2012
DOI: 10.1039/c2dt30147d
|View full text |Cite
|
Sign up to set email alerts
|

Is histidine dissociation a critical component of the NO/H-NOX signaling mechanism? Insights from X-ray absorption spectroscopy

Abstract: The H-NOX (Heme-Nitric oxide/OXygen binding) family of diatomic gas sensing hemoproteins has attracted great interest. Soluble guanylate cyclase (sGC), the well-characterized eukaryotic nitric oxide (NO) sensor is an H-NOX family member. When NO binds sGC at the ferrous histidine-ligated protoporphyrin-IX, the proximal histidine ligand dissociates, resulting in a 5-coordinate (5c) complex; formation of this 5c complex is viewed as necessary for activation of sGC. Characterization of other H-NOX family members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 58 publications
6
19
0
1
Order By: Relevance
“…Many bacterial H-NOX domains have now been cloned, expressed, purified, and spectroscopically characterized (Arora & Boon, 2012; Boon et al, 2006; Dai, Farquhar, Arora, & Boon, 2012; Henares et al, 2012; Karow et al, 2004; Liu et al, 2012; Ma, Sayed, Beuve, & van den Akker, 2007; Mukhopadyay, Sudasinghe, Schaub, & Yukl, 2016; Price, Chao, & Marletta, 2007; Tsai, Berka, Martin, & Olson, 2012; Tsai et al, 2010; Wang et al, 2010; Wu, Liu, Berka, & Tsai, 2015). UV/vis spectroscopy, paired with resonance Raman (rR) spectroscopy, has demonstrated that ferrous H-NOX domains from facultative aerobes form high-spin 5-coordinate Fe(II)-unligated complexes (Boon et al, 2006; Karow et al, 2004).…”
Section: Ligand-binding Properties Of H-nox Domainsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many bacterial H-NOX domains have now been cloned, expressed, purified, and spectroscopically characterized (Arora & Boon, 2012; Boon et al, 2006; Dai, Farquhar, Arora, & Boon, 2012; Henares et al, 2012; Karow et al, 2004; Liu et al, 2012; Ma, Sayed, Beuve, & van den Akker, 2007; Mukhopadyay, Sudasinghe, Schaub, & Yukl, 2016; Price, Chao, & Marletta, 2007; Tsai, Berka, Martin, & Olson, 2012; Tsai et al, 2010; Wang et al, 2010; Wu, Liu, Berka, & Tsai, 2015). UV/vis spectroscopy, paired with resonance Raman (rR) spectroscopy, has demonstrated that ferrous H-NOX domains from facultative aerobes form high-spin 5-coordinate Fe(II)-unligated complexes (Boon et al, 2006; Karow et al, 2004).…”
Section: Ligand-binding Properties Of H-nox Domainsmentioning
confidence: 99%
“…Extended X-ray absorption fine structure (EXAFS) measurements of H-NOX from several species known to form 5- or 6-coordinate complexes with NO were determined (Dai et al, 2012). Shewanella woodyi and Pseudoalteromonas atlantica H-NOX proteins are known to form 5-coordinates complexes with NO (Arora & Boon, 2012; Liu et al, 2012), which is consistent with dissociation of the proximal histidine.…”
Section: Structure and The Molecular Basis For Function In H-nox Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuere Studien diskutieren jedoch, dass zur Auslçsung der Signaltransduktion unter Umständen keine vollständige Dissoziation notwendig ist. [135] Die Konformationsänderung in der H-NOX-Domäne setzt sich in die heterodimere katalytische Domäne fort, wodurch die Produktion von cGMP verstärkt wird. Als Bindeglied zwischen der NO-Bindung und der sGC-Aktivierung wurde eine Spannungsverminderung des Häm-Kofaktors bei der Dissoziation von His105 (oder Verlängerung der Fe-His-Bindung) in Kombination mit Bewegungen der N-Termini vorgeschlagen [136] und mit einer sich entspannenden Feder bildhaft verglichen.…”
Section: Guanylatcyclaseunclassified